Thrombocytopenia and its association with mortality in patients with COVID‐19 - Yang, Xiaobo; Yang, Qingyu; Wang, Yaxin; Wu, Yongran; Xu, Jiqian; Yu, Yuan; Shang, You (Journal of thrombosis and haemostasis, 2020)
Background Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which causes novel coronavirus disease 2019 (COVID‐19), is spreading rapidly around the world. Thrombocytopenia in patients with COVID‐19 has not been fully studied. Objective To describe thrombocytopenia in patients with COVID‐19. Methods For each of 1476 consecutive patients with COVID‐19 from Jinyintan Hospital, Wuhan, China, nadir platelet count during hospitalization was retrospectively collected and categorized into (0, 50], (50, 100], (100‐150], or (150‐) groups after taking the unit (×109/L) away from the report of nadir platelet count. Nadir platelet counts and in‐hospital mortality were analyzed. Results Among all patients, 238 (16.1%) patients were deceased and 306 (20.7%) had thrombocytopenia. Compared with survivors, non‐survivors were older, were more likely to have thrombocytopenia, and had lower nadir platelet counts. The in‐hospital mortality was 92.1%, 61.2%, 17.5%, and 4.7% for (0, 50], (50, 100], (100‐150], and (150‐) groups, respectively. With (150‐) as the reference, nadir platelet counts of (100‐150], (50, 100], and (0, 50] groups had a relative risk of 3.42 (95% confidence interval [CI] 2.36‐4.96), 9.99 (95% CI 7.16‐13.94), and 13.68 (95% CI 9.89‐18.92), respectively. Conclusions Thrombocytopenia is common in patients with COVID‐19, and it is associated with increased risk of in‐hospital mortality. The lower the platelet count, the higher the mortality becomes.